If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-4(8w -7) = -30w + 10
We simplify the equation to the form, which is simple to understand
-4(8w-7)=-30w+10
Reorder the terms in parentheses
+(-32w+28)=-30w+10
Remove unnecessary parentheses
-32w+28=-30w+10
We move all terms containing w to the left and all other terms to the right.
-32w+30w=+10-28
We simplify left and right side of the equation.
-2w=-18
We divide both sides of the equation by -2 to get w.
w=9
| 6-y=25 | | 3x^2-24x=-2x^2-7x-6 | | 4x+6=-12 | | 3x+25=61 | | 90-2x=80-x | | 8*-7+3=5*-7-18 | | x+2+3=270 | | 5x+48+7x=12(x-4) | | y^2-10y+25=3-x | | (9x+2)(3x^2-20x-7)=0 | | y=-2x^2-2x-3 | | 9x-32=9x-33 | | -2=8x | | 39=3(2x-1) | | 15-(-11)= | | 5(2b+1)=25 | | 8b-1=3 | | 7a-6-6a=3+1 | | -54+18= | | 6(-5)= | | 32=3y-7 | | r+16=5r+10 | | 2+t=27-4T | | 3v^2+23v+40=0 | | 6(x+y)+(x-y)= | | 8x+25=3x+145 | | 7-2(m+1)= | | 107-2x=34x+15 | | 8-8x=58-43x | | (2x+3)-1=6 | | 4x-39=647 | | y=4E+07 |